Optimization Strategy for Short Video Content Generation on the Tik Tok Platform - Hu Taijie (SHS Web of Conferences)
In today’s society, with the popularity of TikTok, digital marketing has also begun to develop rapidly with the rise of short videos, and the content of short videos has also become important. This paper mainly studies the key points of short video content generation and optimization on the TikTok platform. This paper will complete this study by referring to different literature and comparing different examples. Through the study and summary of these key points, some suggestions are provided for the optimization of short video content on the TikTok platform in the future. The study emphasizes the importance of audio-visual quality in improving the quality of short videos, and also points out that short videos containing hot topics will be more likely to be seen by more people, thereby expanding the reach and influence of the video. However, some so-called popular videos are full of crudely made stalks, which are usually lacking in knowledge and innovation and are offensive. Due to the exaggerated dissemination of the TikTok platform, a bad stalk may be watched by a large number of people. However, a bad stalk itself does not have any positive value and may cause a decline in social morality. Therefore, some users begin to reject the TikTok short video platform. In order to prevent user loss, the research goal of this paper is to “optimize the algorithm of the TikTok platform” so that people can more easily see high-quality videos.